CLEAR: Cache Lines Error Accumulation Reduction by exploiting invisible accesses. (August 2019) - Farbeh, Hamed; Monazzah, Amir Mahdi Hosseini
Abstract: SRAM caches are the most vulnerable processor component to radiation-induced soft errors. Error-Correcting Codes (ECCs) are the conventional scheme to protect caches against soft errors. These errors in the shape of Single-Event Upset (SEU), in which single bit or multiple adjacent bits are affected, can be correctable by ECCs. However, conventional ECCs are unable to correct temporal MBUs (Multiple-Bit Upset), in which two or more SEUs are accumulated in a data word over time. This paper proposes CLEAR (Cache Lines Error Accumulation Reduction) scheme to reduce the occurrence probability of temporal MBUs. By exploiting inherently available externally invisible accesses to all cache ways in a read request, CLEAR conducts more frequent ECC checking for each data word. Therefore, the ECC checking intervals are shortened, which leads to a significant reduction in occurrence probability of temporal MBUs. The evaluations show that CLEAR increases the Mean Time To Failure (MTTF) of the cache by more than 4× compared to the conventional cache architecture with negligible overheads.